10PPrognosis and effect of adjuvant treatment in small, node(-), HER2(+) breast cancer. (24th November 2019) - Lim, S; Sohn, J; Kim, G; Moon, Y; Kim, J H
Abstract: Background: There remains uncertainty regarding prognosis and treatment effect in small, node negative breast cancer. We described overall prognosis of small (<1cm), node (-), HER2 (+) breast cancer after curative surgery, and effect of adjuvant treatment. There remains uncertainty regarding prognosis and treatment effect in small, node negative breast cancer. We described overall prognosis of small (<1cm), node (-), HER2 (+) breast cancer after curative surgery, and effect of adjuvant treatment. Methods: We identified patients who fulfilled inclusion criteria (curative surgery, <1cm, N0, and HER2(+) breast cancer) by medical chart review. We collected data of baseline characteristics, receptor status, surgical method, histologic type, histologic and nuclear grade, adjuvant treatment (chemotherapy, radiotherapy, endocrine therapy, and trastuzumab. We compared baseline characteristics between patients with or without adjuvant treatment (Chi-square), and the prognosis between them (Kaplan meier curve and log-rank test). SPSS version 18.0 was used for statistical analysis. Results: A total of 429 patients (pT1a=205, pT1b=222) were identified. In patients with pT1a, only 1 patient experienced systemic recurrence and death. No difference was observed in DFS and OS between patients with adjuvant chemotherapy and/or adjuvant trastuzumab. In pT1b, HR(-) patients (N = 52), longer DFS was observed in patients who received adjuvant chemotherapy (p = 0.013). There was no difference in DFS according to trastuzumab treatment (p = 0.441). No difference was found according to adjuvant treatment in overall or HR(+) pT1b patients. Conclusions: In conclusion, our result showed overall prognosis of small(<1cm), node (-), and HER2+ breast cancer and patients with pT1b and HR(-) patients can benefit from adjuvant chemotherapy. Subsequent study with large sample size is warranted. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.